Potato breeding Network for Africa - Mendes, T.; Retta, A.; Nduwumuremyi, A.; Egesi, C.; Milic, D.; Kigwinya, K.; Namugg, P.; Otieno, S. (International Potato Center, 2023)
Potatoes are an indispensable crop for East Africa, serving a multitude of vital purposes. They are a staple food crop in many countries, acting as a key source of nutrition for millions of people in the region. This high-energy food provides a significant portion of daily caloric intake, ensuring food security and combating hunger. Also, they are a valuable cash crop for smallholder farmers, providing a source of income throughout the year, come rain or shine. Potatoes offer abundant employment opportunities for people in East Africa, from farmers and traders to processors. Additionally, intercropping potatoes with other crops diversifies agricultural, production and mitigates the risks associated with a reliance on a single crop. Finally, potatoes are important for climate resilience in the region, with their drought and heat tolerance and ability to thrive in diverse agroecological zones. Breeding programs can improve potato varieties, enhancing yields, resistance to pests and diseases, and nutritional content, ultimately supporting the well-being and livelihoods of the people in East Africa.